2013
DOI: 10.1371/journal.pone.0062107
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidia and Its Relation to Crohn's Disease. A Retrospective Study

Abstract: BackgroundThe cause of Crohn's Disease (CD) remains unknown. Recently a decrease in the global lymphocyte population in the peripheral blood of CD patients has been reported. This decrease was more evident in γδ T lymphocytes, especially γδ CD8+T subsets. Furthermore, a decrease of IL-7 was also observed in these patients. We propose the hypothesis that microsporidia, an obligate intracellular opportunistic parasite recently related to fungi, in CD patients can take advantage of the lymphocytes and IL-7 defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…Both Immunocompromised and immunocompetent populations are affected with this infection, with data on microsporidia presence not only in HIV/AIDS patients [16], [17], [18] but also in HIV-negative patients including travelers [19], the elderly [20], organ transplant recipients [21], Crohn’s disease patients [22] and the immunocompetent population [23]. Similar to data described worldwide, E. bieneusi is the species most frequently identified.…”
Section: Introductionsupporting
confidence: 56%
“…Both Immunocompromised and immunocompetent populations are affected with this infection, with data on microsporidia presence not only in HIV/AIDS patients [16], [17], [18] but also in HIV-negative patients including travelers [19], the elderly [20], organ transplant recipients [21], Crohn’s disease patients [22] and the immunocompetent population [23]. Similar to data described worldwide, E. bieneusi is the species most frequently identified.…”
Section: Introductionsupporting
confidence: 56%
“…On the other hand, it is widely accepted that microsporidia cause opportunistic infections in immunocompromised subjects [38-40]. In a previous study [16], we demonstrated the presence of increased anti- Encephalitozoon specific IgE antibodies in the serum of patients with CD. The presence of these microsporidia was identified by PCR in 30% of the tissues of these patients, compared with its absence in healthy patients.…”
Section: Discussionsupporting
confidence: 49%
“…These innate immune deficits make CD patients a group at risk of opportunistic agents involved as possible etiologic factors for CD [16]. B1 lymphocytes are part of innate immunity, which is related, as discussed above, with the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although Microsporidia was detected within the mucosa in almost all cases including nIBD controls, it was only in the Crohn's disease group that there was a statistically significant increase within the submucosa as compared to the mucosa (p = 0.04). These findings may support microspordiosis as a compounding factor in Crohn's disease [ 20 ].…”
Section: Resultsmentioning
confidence: 72%